The Influence Of Financial Attitudes And Financial Self Efficacy On The Personal Financial Management Of Krupuk Industry Employees In Tulangan District (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to examine how financial attitudes and financial self-efficacy influence the personal financial management of employees of the cracker industry in Tulanagan district. The following study is a quantitative quantitative study with a descriptive approach. 158 respondents were taken by purposive sampling from a population of 203 employees. Variables were measured using a Likert scale with a weight range of 1 to 5. Data analysis was carried out by applying Partial Least Square (PLS). The study findings indicate that: (1) financial attitudes have a positive impact on personal financial management (2) financial self-efficacy has a positive impact on personal financial management, (3) financial attitudes and financial self-efficacy simultaneously influence personal financial management.
Keywords: financial attitudes, financial self-efficacy, personal financial management